Hermeneutika dan Ilmu Tafsir: Menelaah Polemik Penerimaan dan Penolakan Metodologi Barat dalam Studi Al-Qur'an - Muklis Siregar; Hasyimsyah Nasution; Zulkarnaen Zulkarnaen (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
The use of hermeneutics in Qur'anic studies has long generated debate among Muslim scholars. Some view hermeneutics as a methodological tool that can bridge the historical distance between the revealed text and contemporary life, whereas others regard it as an epistemological threat that may weaken the authority of the Qur'an. This article aims to analyze the arguments of both proponents and critics and to identify possible areas of convergence. Using a descriptive-analytical approach and library research, this study examines relevant works by scholars who support and oppose the application of hermeneutics in Qur'anic interpretation. The findings show that proponents, such as Fazlur Rahman, Nasr Hamid Abu Zayd, and Mohammed Arkoun, argue that hermeneutics can enrich interpretive methods and help contextualize meaning. Conversely, critics, such as Adian Husaini and scholars who emphasize the authority of established tafsir traditions, argue that hermeneutics emerged from the problems of Biblical interpretation and therefore cannot be applied directly to the Qur'an, which is believed to retain its authenticity. The study concludes that the debate stems from different theological assumptions about text, revelation, and interpretation. It recommends the selective adaptation of hermeneutics as a supporting analytical tool, not as a replacement for the science of tafsir.